The Use of Social Media As a Learning Tool for Islamic Religious Education - Syaikhu, Ach; Z, Rijal Mumazziq; Shalihah, Imra'atus (FALASIFA : Jurnal Studi Keislaman, 2024)
Islamic Religious Education is an essential component in developing the character and spirituality of individual Muslims. In this digital era, social media has become the main platform used as a tool to disseminate religious education. This study aims to analyze the use of social media as a means of learning Islamic religious education through a literature review. The method used is a systematic literature review of various related academic sources. The results show that social media is effective in disseminating Islamic religious education with various types of interactive content, although there are challenges in ensuring the accuracy and quality of information. The conclusion of this study emphasizes the importance of monitoring and regulating religious content on social media to maximize its benefits and minimize the risk of misinformation.